Type 2 calreticulin mutations activate ATF6 to promote BCL-xL–mediated survival in myeloproliferative neoplasms - Arellano, Nicole S.; Heaton, William L.; Nauman, Mirielle C.; Runnels, Abigail E.; Gomez-Villa, Jacky; Vanni, Daniele; Gaviria, Melissa; Fujita, Maihi; Krah, Nathan M.; Ciboddo, Michele; Yadav, Saveg; Brown, Callie T.; et al. (Blood, 2025)
•Type 2 CALRins5 mutations in myeloproliferative neoplasms uniquely activate the ATF6 pathway of the UPR.•CALRins5-mediated ATF6 activation leads to upregulation of B-cell lymphoma extra large, representing a novel therapeutic intervention. [Display omitted] Most calreticulin (CALR) mutations in myeloproliferative neoplasms are classified as either type 1, a 52–base pair deletion (CALRdel52); or type 2, a 5–base pair insertion (CALRins5). Both are gain-of-function (GOF) mutations that generate an identical mutant C-terminal tail, which mediates the binding to, and activation of, the thrombopoietin receptor myeloproliferative leukemia protein (MPL). We recently reported that despite this shared GOF, CALRdel52 but not CALRins5 mutations cause loss of calcium binding function, leading to activation of, and dependency on, the inositol-requiring enzyme 1/X-box binding protein 1 pathway of the unfolded protein response (UPR). This led us to ask whether CALRins5 mutations activate and depend on a different UPR pathway, and whether this is likewise mediated by a mutation type–specific loss-of-function (LOF). Here, we show that CALRins5 mutations lead to activation of the activating transcription factor 6 (ATF6) pathway of the UPR due to loss of CALR chaperone function. This LOF is caused by interference of the CALRins5 mutant C terminus with key chaperone residue H170. Furthermore, we show that CALRins5 cells are partially dependent on ATF6 for cytokine-independent growth, and identify B-cell lymphoma extra large as a transcriptional target of ATF6 that promotes type 2 CALR-mutant cell survival. Both CALRdel52 (type 1) and CALRins5 (type 2) mutant calreticulins bind the thrombopoietin receptor and activate JAK/STAT signaling driving myeloproliferative neoplasia, but biologically the mutations are not functionally identical. Arellano et al report that type 2 CALR mutations, but not type 1 mutations, stimulate activating transcription factor 6 (ATF6), leading to upregulation of the antiapoptotic protein BCLxL. Type 2 mutant cells are highly dependent on ATF6 and sensitive to BCLxL inhibition but insensitive to BCL2 inhibition. This work reveals a potential therapeutic vulnerability in type 2 CALR-mutant myeloproliferative neoplasms.